A Role for Information Collection, Management, and Integration in Structure-Function Studies of G-Protein Coupled Receptors - Shi, Lei; Javitch, Jonathan A. (Current Pharmaceutical Design, 2006)
Elucidation of protein function is greatly facilitated by the availability of an atomic resolution structure or a reliable molecular model. The difficulty of obtaining atomic resolution structures of membrane proteins in general, and of G-protein coupled receptors (GPCRs) in particular, has made the information available from sequence analysis, mutagenesis, and the literature on related GPCRs exceptionally important. Here, we review previous studies of GPCR structurefunction from the perspectives of sequence analysis, management of mutagenesis and ligand binding data, and literature data mining. The knowledge derived from these information resources not only constitutes the prerequisites for reliable molecular modeling, but also can provide other insights into GPCR functions. Finally, we review approaches for information integration and applying knowledge discovery techniques to structure-function studies of GPCRs, including molecular modeling itself.
Keywords: Correlated mutations